EVOLUTION OF ICT IN ENGLISH LANGUAGE LEARNING - Margaret Samuelson Udoh (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
Technology has become increasingly integrated into English language classrooms over time. The use of information and communication technology has expanded into many contexts of ELT. (ELT). From CALL to MALL to RALL to TELL, this paper will try to trace the evolution of ICT use in ELT and the approaches that were pursued at each stage. Learners have not been spared the various challenges that come with the use of technology in any shape, despite the long journey of ICT in language teaching from the 1970s. These difficulties are highlighted, and potential solutions are proposed.